Detection of pesticides in the peach (prunus pérsica) by an electronic nose - Rivera-Guerrero, Manuel Andrés; Gualdrón-Guerrero, Oscar Eduardo; Torres-Chávez, Ivaldo (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of this work is to explore the possibilities of a multisensory system, electronic nose type, for the detection of organophosphorus pesticides in the peach tree (Prunus persica), cultivated in the department of Norte de Santander, Colombia. The tests were performed with an electronic nose consisting of 8 chemical-resistive sensors, and the method of processing used was the principal component analysis (PCA). Initially it was observed that the sensors react to the volatile compounds present in the peach, without the presence of pesticides. By adding known concentrations of pesticides to the fruit, it was possible to group the samples into four groups, like this: without pesticides, 1, 2 and 3 ppm. The above indicates that the system used allows differentiating pure samples from contaminated ones, in addition to grouping the different concentration ranges. It concludes with the possibility of using the electronic nose, in the quality control of agricultural products.